My world - Santos, Manuel dos (McGraw-Hill ESL/ELT, 2006)
Integrates the day-to-day aspects of teenagers' lives with real-life English learning situations and models. This title covers the four skills of reading, writing, listening, and speaking in a meaningful way. It includes theme-based units that appeal to teenagers which combine language input with skills work